The effect of choline availability from gestation to early development on brain and retina functions and phospholipid composition in a male mouse model. (3rd August 2022) - Alashmali, Shoug; Walchuk, Chelsey; Cadonic, Chris; Albensi, Benedict C.; Aliani, Michel; Suh, Miyoung
ABSTRACT: Objectives: Although choline is essential for brain development and neural function, the effect of choline on retina function is not well understood. This study examined the effects of choline on neural tissues of brain and retina, and membrane phospholipid (PL) composition during fetal development. Methods: Pregnant C57BL/6 mice were fed one of 4 choline modified diets: i) control (Cont, 2.5g/kg), ii) choline deficient (Def, 0g/kg), iii) supplemented with choline chloride (Cho, 10g/kg) and iv) supplemented with egg phosphatidylcholine (PC, 10g/kg). At postnatal day (PD) 21, pups were weaned onto their mothers' respective diets until PD 45. Spatial memory was measured using the Morris Water Maze; retina function by electroretinogram (ERG); and PL composition with nuclear magnetic resonance spectroscopy. Results: Cho and PC supplementation enhanced cued learning and spatial memory abilities, respectively (p Def > PC > Cho, with no statistically significant alterations in cone-driven responses. There were no differences in the composition of major PLs in the brain and retina. In the brain, subclasses of ether PL, alkyl acyl- phosphatidylethanolamine (PEaa) and phosphatidylcholine (PCaa) were significantly greater among the PC supplemented group in comparison to the Def group. Discussion: These results indicate that while choline supplementation during gestation to an early developmental period is beneficial for spatial memory, contributions to retina function are minor. Assessment with a larger sample size of retinas could warrant the essentiality of choline for retina development.